PENDAMPINGAN PENYUSUNAN KATALOG DWI BAHASA INDONESIA – INGGRIS SEBAGAI MEDIA KOMUNIKASI PEMASASAN PRODUK UMKM KAMPUNG KUE RUNGKUT SURABAYA UNTUK WISATAWAN ASING - Marsih, Linusia; Wahyono, Danu; Amalijah, Eva; Supsiadji, Mateus Rudi; Romansa, Erven Nofryan; Wijayanto, Maulana Nero Surya (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Kampung Kue Rungkut is a culinary tourism destination in Surabaya offering a variety of traditional snacks. Since its inauguration as a Culinary Tourism Village in 2022, the area has seen an increase in visits from both domestic and international tourists. However, the challenges faced by Micro, Small, and Medium Enterprise (MSME) actors in Kampung Kue Rungkut are limited marketing communications, particularly in English. This hampers the effectiveness of promotions and services to foreign tourists, who often inquire about the products offered. Based on discussions with MSME owners, there is a need for marketing communication materials that provide written information in both Indonesian and English.Therefore, this community service activity aims to assist MSMEs in improving marketing communications by developing a bilingual Indonesian-English catalog for Kampung Kue Rungkut's traditional snacks. This catalog is expected to be an effective means of providing clear and attractive information to tourists and assisting businesses in marketing their products more widely. The method used in this activity is a participatory one, enabling active involvement of the target community in every stage of the activity. This activity has produced a bilingual Indonesian-English catalog containing information on traditional snacks produced by Kampung Kue Rungkut Surabaya.